2022
DOI: 10.14218/jcth.2021.00560
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D Inhibitor Necrosulfonamide Alleviates Lipopolysaccharide/D-galactosamine-induced Acute Liver Failure in Mice

Abstract: Background and Aims: Acute liver failure (ALF) is associated with high mortality. Gasdermin D (GSDMD) is the executioner of pyroptosis and is involved in the pathophysiology of immune dysregulation This study investigated the role of the GSDMD inhibitor necrosulfonamide (NSA) in ALF. Methods: An ALF model was established by lipopolysaccharide/D-galactosamine challenge in C57BL/6J mice. Mice were divided into four groups: normal controls (control group), ALF group (ALF group), dimethyl sulfoxide group (DMSO gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…aureus and E. coli, employing necrosulfonamide (NSA) as a GSDMD-NT protein inhibitor, to evaluate the antimicrobial effect of GSDMD-NT protein . The results obtained from SPM for assessing CFUs revealed significant antimicrobial effects in the PCZs and PCZs + NIR treatment groups, while the addition of NSA diminished the antimicrobial effect but still remained higher than that of the Control group (Figure j,k).…”
Section: Results and Discussionmentioning
confidence: 98%
“…aureus and E. coli, employing necrosulfonamide (NSA) as a GSDMD-NT protein inhibitor, to evaluate the antimicrobial effect of GSDMD-NT protein . The results obtained from SPM for assessing CFUs revealed significant antimicrobial effects in the PCZs and PCZs + NIR treatment groups, while the addition of NSA diminished the antimicrobial effect but still remained higher than that of the Control group (Figure j,k).…”
Section: Results and Discussionmentioning
confidence: 98%
“…Another study indicates that NSA inhibits the pyroptosis pathway in ALF, leading to an increased survival rate in ALF mice. However, the study did not determine whether these pyroptotic cells are primarily hepatocytes or macrophages ( 116 ). Therefore, targeting GSDMD-NT oligomerization has shown promising results in inflammatory and autoimmune liver diseases.…”
Section: Targeted Inhibition Of Macrophage Pyroptosis In the Treatmen...mentioning
confidence: 99%
“…Recent evidence has challenged the specificity of necrosulfonamide by showing that in addition to MLKL-mediated necroptosis, necrosulfonamide also inhibits GSDMD-induced pyroptosis (144). Following this report, several studies showed that necrosulfonamide prevented disease outcomes in mouse models of diseases such as acute brain injury, colitis, acute liver failure, and myocardial dysfunction due to its pyroptosis inhibitory effects (144)(145)(146)(147). Recently, a new class of xanthine and uracil derivatives has been reported to stabilize the inactive state of MLKL, thereby inhibiting MLKL oligomerization and membrane translocation, but their precise mechanism of action, in vivo safety, and off-target effects remain to be elucidated (148,149).…”
Section: Mlkl As a Potential Future Therapeutic Targetmentioning
confidence: 99%